Designing Storynomics Agritourism at Batungsel Village, Tabanan Regency, Bali - Jayantini, I Gusti Agung Sri Rwa; Martiningsih, Ni Gusti Agung Gde Eka; Wiratama, I Gusti Ngurah Made; Karta, Ni Luh Putu Agustini (IJCS: International Journal of Community Service, 2024)
Storynomics tourism is about packaging the beautiful charm of a tourist destination in an interesting story, so that it becomes an attraction for foreign tourists visiting places of interests in Indonesia. Every tourist destination in Indonesia has its own uniqueness and this can be packaged in the form of storynomics tourism which can promote tourism and the creative economy in Indonesia. The training and consultation of designing agritourism attraction programs with storynomics values reported in this paper aimed at preparing tourism programs, i.e. branding for Kampung Kopi Camp (KKC) and Yeh Nu Garden (YNG), two interesting tourist attractions at Batungsel village, Pupuan subdistrict, Tabanan regency, Bali province. Designing storynomics agritourism at Batungsel Village, Tabanan Regency, Bali was realized through several stages, namely (1) compiling tour packages connecting one place to another with the close routes, (2) telling the stories about Robusta coffee roasting and its local wisdom, and (3) developing agritourism high quality fruits at Batungsel village. All of these steps were applied in accordance with the main focus of the Community Empowerment Program designed to develop agritourism at the rural area of Bali.